Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat pada Lansia Penderita Hipertensi di Rumah Sakit Sari Asih Tangerang - Ria Rachmasari, Ria Rachmasari; Iwan Ardian; Iskim Lutfha (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Hypertension is a chronic condition with a high prevalence among the elderly population and is often overlooked despite its potential to cause severe complications, including cardiovascular disease, stroke, and kidney damage. Effective management of hypertension requires not only pharmacological treatment but also patient adherence to prescribed therapies, which is closely linked to their knowledge and understanding of the disease. This study aims to analyze the relationship between knowledge levels and medication adherence among elderly hypertension patients at Sari Asih Hospital in Tangerang. A quantitative approach with a cross-sectional design was employed, and a total of 80 respondents were selected using non-probability sampling techniques. Data were collected using structured questionnaires that assessed both knowledge about hypertension and adherence to medication regimens. Statistical analysis was conducted using Kendall’s tau correlation, which revealed a strong and significant relationship between knowledge and medication adherence (τ = 0.759, p = 0.000). These findings indicate that elderly patients with higher levels of knowledge about hypertension are more likely to adhere to their medication schedules consistently, thereby reducing the risk of complications. The results underscore the importance of continuous health education and counseling for elderly patients to strengthen their awareness and self-management skills. In conclusion, increasing knowledge through targeted health promotion programs can play a vital role in improving adherence to hypertension treatment and ultimately enhancing patient outcomes.